Psychosocial and spiritual training to improve the Indonesian Migrant Workers (IMW) wellbeing in Taiwan - Laili Nur Hidayati; Ferika Indarwati; Fahni Haris; Maulana M. Yusuf Efendi (Journal of Community Service and Empowerment, 2023)
The high number of uneducated Indonesian Female Migrant Workers (FMW) in Taiwan makes migrant workers a vulnerable group to receive discriminatory treatment, to get less access to health services, and to experience sexual violence or harassment. Psychological problems and lack of family support for IMWs are exacerbated by low literacy skills. The aim of this community service training is to improve the IMWs wellbeing. The training was followed by 16 migrant workers. Prior to the training program, the pre-test result showed that the lowest score of the participants was 5 and the highest score was 14. The average score of the participants' pre-test was 9.72. After the training activities were completed, a post-test was conducted to determine if there will be any changes in knowledge. The results of the post-test indicated that the lowest score of participants is 10 and the highest 15. The average post-test score of participants was 13.27. Based on the test results, it can be concluded that there is an increase in the average test score given, with an increase of 3.55. Participants who took part in the training experienced an increase in knowledge related to the topics of the training material provided. Therefore, assessment and training related to language or communication, occupational health, psychosocial health, and job skills training are needed to be improved for the FMW.